VISUAL IDENTITY IN DESTINATION BRANDING BLENDUK CHURCH AREA, SEMARANG - Santi Widiastuti (Pixel :Jurnal Ilmiah Komputer Grafis, 2021)
This study aims to analyze the potential of the Blenduk church area in Semarang. The potential of this area needs a visual identity design as a form of tourism promotion in the city of Semarang, which incidentally the government is still active in increasing the promotion of local tourism. This study intends to design a visual identity for the Blenduk church area, so this research was carried out with qualitative research. As a persuasive communication activity, this design uses the A-A Procedure approach. The data collection techniques in this study were observation, interviews, documentation and literature study. This study intends to contribute to the Semarang city government, especially the Culture and Tourism office, to design the visual identity of the Blenduk church area so that it has an identity that can be sold to the public and can increase the attractiveness of stakeholders to increase